Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3389/fpls.2014.00537
|View full text |Cite
|
Sign up to set email alerts
|

Flowering time control in European winter wheat

Abstract: Flowering time is an important trait in wheat breeding as it affects adaptation and yield potential. The aim of this study was to investigate the genetic architecture of flowering time in European winter bread wheat cultivars. To this end a population of 410 winter wheat varieties was evaluated in multi-location field trials and genotyped by a genotyping-by-sequencing approach and candidate gene markers. Our analyses revealed that the photoperiod regulator Ppd-D1 is the major factor affecting flowering time in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
116
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(136 citation statements)
references
References 67 publications
10
116
2
3
Order By: Relevance
“…It was reported that wheat genotypes with all three dominant alleles of Vrn-1 genes (Vrn-A1, Vrn-B1, and Vrn-D1) head quite early compared to mono-or di-dominant gene combinations [28]. Similar information was also reported by various authors [5,9,[57][58][59]. From the results of the above-mentioned studies, it was shown which combinations of alleles perform better than others.…”
Section: The Interaction Of Vrn and Ppd Alleles And Its Impact On Flosupporting
confidence: 76%
See 4 more Smart Citations
“…It was reported that wheat genotypes with all three dominant alleles of Vrn-1 genes (Vrn-A1, Vrn-B1, and Vrn-D1) head quite early compared to mono-or di-dominant gene combinations [28]. Similar information was also reported by various authors [5,9,[57][58][59]. From the results of the above-mentioned studies, it was shown which combinations of alleles perform better than others.…”
Section: The Interaction Of Vrn and Ppd Alleles And Its Impact On Flosupporting
confidence: 76%
“…A moderate but significant correlation between flowering time and plant height has been reported in bread wheat [5,[80][81][82]. Shorter genotypes tend to flower earlier than the taller ones [5].…”
Section: The Influence Of Height-reducing Genes On the Flowering Timementioning
confidence: 99%
See 3 more Smart Citations